Defining a minimal cell: essentiality of small ORFs and ncRNAs in a genome‐reduced bacterium. Issue 1 (21st January 2015) - Lluch‐Senar, Maria; Delgado, Javier; Chen, Wei‐Hua; Lloréns‐Rico, Verónica; O'Reilly, Francis J; Wodke, Judith AH; Unal, E Besray; Yus, Eva; Martínez, Sira; Nichols, Robert J; Ferrar, Tony; Vivancos, Ana; et al.
Abstract: Identifying all essential genomic components is critical for the assembly of minimal artificial life. In the genome‐reduced bacterium Mycoplasma pneumoniae, we found that small ORFs (smORFs; < 100 residues), accounting for 10% of all ORFs, are the most frequently essential genomic components (53%), followed by conventional ORFs (49%). Essentiality of smORFs may be explained by their function as members of protein and/or DNA/RNA complexes. In larger proteins, essentiality applied to individual domains and not entire proteins, a notion we could confirm by expression of truncated domains. The fraction of essential non‐coding RNAs (ncRNAs) non‐overlapping with essential genes is 5% higher than of non‐transcribed regions (0.9%), pointing to the important functions of the former. We found that the minimal essential genome is comprised of 33% (269, 410 bp) of the M. pneumoniae genome. Our data highlight an unexpected hidden layer of smORFs with essential functions, as well as non‐coding regions, thus changing the focus when aiming to define the minimal essential genome. Synopsis: A genome essentiality analysis in the genome‐reduced bacterium Mycoplasma pneumoniae, reveals that protein essentiality should be considered at the domain level and that small proteins (< 100 aa) and ncRNAs are frequently essential genomic elements. A genome essentiality analysis is performed using two mini‐transposon mutant libraries of M. pneumoniae . The results indicate that ORF essentiality should be considered at the protein domain level. Small ORFs are as essential as conventional ORFs and they can interact with DNA. Some essential antisense ncRNAs are involved in the regulation of essential ORF expression. Abstract : A genome essentiality analysis in the genome‐reduced bacterium Mycoplasma pneumoniae, reveals that protein essentiality should be considered at the domain level and that small proteins (< 100 aa) and ncRNAs are frequently essential genomic elements.